O uso do conhecimento tecnológico, pedagógico e de conteúdo integrado a Taxonomia Digital de Bloom para o ensino de química - Wentz, Fabiane Malakowski de Almeida (2018)
This research entitled "The use of the technological, pedagogical and content knowledge integrated in the Digital Taxonomy of Bloom for the teaching of chemistry" was developed in the research group LAEQUI of the Graduate Program in Teaching Sciences: Chemistry of Life and Health of the University Federal de Santa Maria / RS, having as research line - Scientific Education: teaching and learning processes in school, university and research laboratory. It is characterized by being a predominantly qualitative research, which used as strategy the elaboration of a planning that integrated the TPACK and Digital Taxonomy of Bloom, that are reached with the use of digital tools in the different levels of learning of the cognitive development of the students . This work was developed with students of the third year of High School of a state school of Santo Ângelo-RS, through the thematic "Agrotóxicos" with approach in the content of organic functions. The research was developed in two stages. In the first stage we sought theoretical references for the construction and evaluation of the planning based on the TPACK development and the Bloom Digital Taxonomy. The second stage was directed to the classroom application of the planning allied to the learning objectives considering cognitive levels of the Bloom Digital Taxonomy. The interventions were planned for each level and validated by a group of researchers using a TPACK Assignment rubric and also for student-built assessment of learning. These interventions were planned using videos, virtual murals, discussion forums, games, internet searches, bookmarking, e-mail, spreadsheets, online questionnaires and software on conceptual maps such as digital resources. The results of this research were obtained through different data collection instruments, such as: questionnaires, textual productions, different activities with the use of digital resources of the interventions, conceptual maps, video production and observations and annotations of the researcher, which were analyzed according to the Discursive Textual Analysis. It is concluded that these resources should be explored by the teachers, since they are facilitators for the construction of the process of teaching and learning with the use of technologies. In addition, the results obtained allowed to conclude by the evaluation of each level of cognitive development, which was favored the learning of scientific and technological concepts, since an evolution was observed not only in the abilities of the cognitive domains, but also a better utilization of resources technological developments.